Secretory immunoglobulins of the Duck (Anas platyrrhynchos domesticus) - Hari Kumar A V (Department of Microbiology, College of Veterinary and Animal Sciences, 1996)
The profile and functional properties of the immunoglobulins of serum, bile, mucos of trachea and intestine of ducks were studied.